A method for degrading microplastics by using a surface hydroxyl modified defective bismuth oxyhalide photocatalytic material

CN119018975BActive Publication Date: 2026-10-27HENAN AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411217879.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2026-10-27
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

3.水资源污染:微塑料颗粒在水体中漂浮、沉积或被生物摄取,导致水生生态污染

Benefits of technology

[0025](1)合成过程中α-D-葡萄糖与BiOCl的质量比分别7%、10%、15%、20%,得到的BiOCl产物分别标记为G/BOC-7、G/BOC-10、G/BOC-15和G/BOC-20。作为对照试验,在不添加葡萄糖的情况下,用相同的方法制备的样品标记为BOC。步骤(2)中α-D-葡萄糖的添加量为15%时,得到的颗粒堆叠的BiOCl光催化剂G/BOC-15性能最佳。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119018975B_ABST
    Figure CN119018975B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of surface hydroxyl modification defect type bismuth oxyhalide photocatalytic material for degrading microplastics method, belong to photocatalytic technical field.The glycol precursor solution of bismuth nitrate pentahydrate and potassium chloride is prepared, a certain amount of glucose (alpha-D-glucose) is dissolved in 10mL water and 10mL ethanol mixed solution, placed in reaction kettle and carried out solvothermal reaction, by changing the content of glucose in mixed solution, the concentration of surface hydroxyl of photocatalyst is controlled, and the best BiOCl photocatalytic material is obtained.The photocatalytic material prepared by the preparation method provided by the present application has excellent catalytic performance, can efficiently accelerate the degradation process of microplastics in water under ultraviolet light, wherein the catalytic performance of G / BOC-15 photocatalyst is the best, the weight loss rate of polystyrene microplastics is 38% in 12 hours, and the application of photocatalytic reaction in wastewater treatment provides good material basis and technical support.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, and specifically relates to the preparation method of defective bismuth halide photocatalytic materials with surface hydroxyl modification and their application in accelerating the photodegradation of microplastics. Background Technology

[0002] Microplastics are plastic particles with a diameter of less than 5 millimeters. Due to their difficulty in decomposition and their tendency to readily adsorb pollutants, they have received widespread attention in recent years. Microplastics mainly originate from the production, use, and disposal of plastic products. They are widely present in water bodies, soil, air, and organisms, posing a serious threat to the ecological environment and human health. The hazards of microplastics are mainly manifested in the following aspects:

[0003] 1. Ecological and Environmental Damage: Microplastics are difficult to decompose in nature and accumulate in ecosystems over time, leading to ecological imbalance. 2. Threats to Human Health: Microplastics enter the food chain, endangering human health. Many foods, such as seafood, bottled water, milk, and coffee, contain microplastic particles. These microplastics, once ingested, may cause diseases of the digestive, cardiovascular, and nervous systems. 3. Water Pollution: Microplastic particles float, settle, or are ingested by organisms in water bodies, causing aquatic ecological pollution. This further threatens terrestrial ecosystems, damaging soil and air, and even affecting Earth's life systems. 4. Reduction in Biodiversity: The accumulation of microplastics in organisms affects their growth, reproduction, and survival rates, thus reducing biodiversity. 5. Environmental Risks: Microplastic particles are dispersed by wind and enter the atmosphere, becoming airborne dust and affecting air quality. Furthermore, the use of personal protective equipment such as masks and gloves exacerbates microplastic pollution. To address microplastic pollution, the Chinese government and all sectors of society should intensify environmental protection publicity efforts, raise public awareness of environmental protection, promote the use of biodegradable plastics, strengthen the recycling and treatment of waste plastics, and reduce the production and use of plastic products, thereby reducing the risk of microplastic pollution. How to efficiently and environmentally degrade microplastics in water remains an urgent problem to be solved. Because microplastics are very stable, traditional water treatment processes cannot effectively remove them. Therefore, there is an urgent need to find efficient and low-cost technologies to eliminate microplastics in aquatic environments.

[0004] In recent years, numerous studies have shown that photocatalysis is a promising treatment technology that can convert organic pollutants into harmless substances under mild conditions. Many researchers are also attempting to develop various highly efficient photocatalysts to decompose microplastics in water.

[0005] Among the many reported photocatalytic materials, bismuth oxychloride (BiOCl) has attracted much attention due to its suitable bandgap structure, simple synthesis method, good chemical stability, and unique layered structure. However, the catalytic ability of BiOCl is limited by drawbacks such as the easy recombination of photogenerated electron-hole pairs, low specific surface area, and narrow photoresponse range. Summary of the Invention

[0006] The technical problem solved by this invention is to provide a method for using a surface-hydroxyl-modified defective bismuth oxychloride (BiOCl) photocatalyst for degrading microplastics. This method is simple to operate and environmentally friendly, enabling the accelerated photodegradation of microplastics using BiOCl photocatalysts. This invention focuses on a surface-hydroxyl-modified defective BiOCl photocatalyst, investigating the differences in surface hydroxyl photofunctional modification amount and catalytic performance of BiOCl photocatalysts prepared by different synthesis processes (content of reducing α-D-glucose). A simple and effective method for synthesizing G / BOC-15 photocatalysts is proposed, which can effectively degrade typical microplastics such as polystyrene microplastics (PS-MPs), providing a new method for wastewater treatment and environmental protection. The presence of G / BOC-15 results in the highest weight loss rate for PS-MPs, achieving a 38% weight loss rate within 12 hours, demonstrating excellent catalytic degradation performance for PS-MPs.

[0007] To solve the technical problem of this invention, the proposed technical solution is: a method for using a surface hydroxyl-modified defective bismuth halide photocatalytic material to degrade microplastics, the specific steps of which are as follows:

[0008] (1) Add Bi(NO3)3·5H2O and potassium chloride in a mass ratio of 1:1 to a mixture of ethanol and water;

[0009] (2) Dissolve a certain amount of α-D-glucose in a mixture of water and ethanol, with a volume ratio of water to ethanol of 1:1.

[0010] (3) Then add the glucose solution prepared in step (2) to the mixture in step (1) and stir continuously for 60 min;

[0011] (4) Transfer the final solution to a polytetrafluoroethylene high-pressure reactor, and then heat it to 100-150℃ for hydrothermal reaction for 10h;

[0012] (5) Collect the product obtained in step (4), rinse it alternately with deionized water and ethanol, and then dry it overnight in a drying oven at 60°C. The mass ratio of α-D-glucose to BiOCl is 15%, and the obtained BiOCl product is labeled as G / BOC-15.

[0013] (6) Under the action of a 500W Hg lamp, 0.5g / L of photocatalyst G / BOC-15 was added to the polystyrene microplastic PS-MPs solution, and the photocatalytic degradation of the microplastic PS-MPs was carried out using a photoreaction instrument.

[0014] Preferably, the specific steps are as follows:

[0015] (1) Add 4.8 mmol of Bi(NO3)3·5H2O and 4.8 mmol of potassium chloride to a mixture of 28 mL of ethanol and 12 mL of water;

[0016] (2) Dissolve 0.1875 g of α-D-glucose in a mixture of water and ethanol, with a volume ratio of water to ethanol of 1:1.

[0017] (3) Then add the glucose solution prepared in step (2) to the mixture in step (1) and stir continuously for 60 min;

[0018] (4) Transfer the final solution to a polytetrafluoroethylene high-pressure reactor, and then heat it to 100-150℃ for hydrothermal reaction for 10h;

[0019] (5) Collect the product obtained in step (4), rinse it alternately with deionized water and ethanol, and then dry it overnight in a drying oven at 60°C. The mass ratio of α-D-glucose to BiOCl is 15%, and the obtained BiOCl product is labeled as G / BOC-15.

[0020] (6) Under the action of a 500W Hg lamp, 1g / L of micron-sized plastic PS-MPs were dispersed in 100mL of aqueous solution. Then, 0.5g / L of photocatalyst G / BOC-15 was added to the above solution. The photocatalytic degradation of microplastic PS-MPs was carried out using a photocatalytic reaction instrument. After 12 hours of reaction, the light source was turned off, and the solution was filtered using a water system filter membrane with a pore size of 0.45μm.

[0021] Preferably, the prepared particle-stacked G / BOC-15 material exhibits the best performance when the mass ratio of α-D-glucose to BiOCl added in step (2) is 15%.

[0022] Preferably, the morphology of BiOCl and the content of surface hydroxyl functional groups are controlled by changing the amount of α-D-glucose in step (2). The prepared G / BOC-15 photocatalyst has the largest amount of surface hydroxyl modification and oxygen vacancies, and has the best photocatalytic degradation performance of polystyrene microplastics.

[0023] Preferably, under direct ultraviolet irradiation, the presence of G / BOC-15 results in the highest weight loss rate of PS-MPs, achieving a degradation weight loss rate of 38% for PS-MPs within 12 hours, demonstrating excellent catalytic degradation performance for PS-MPs.

[0024] Beneficial effects:

[0025] (1) During the synthesis process, the mass ratios of α-D-glucose to BiOCl were 7%, 10%, 15%, and 20%, respectively, and the resulting BiOCl products were labeled as G / BOC-7, G / BOC-10, G / BOC-15, and G / BOC-20, respectively. As a control experiment, samples prepared using the same method without the addition of glucose were labeled as BOC. In step (2), when the amount of α-D-glucose added was 15%, the resulting particle-stacked BiOCl photocatalyst G / BOC-15 exhibited the best performance.

[0026] (2) This invention employs a simple and feasible preparation method to prepare a BiOCl photocatalyst capable of effectively degrading microplastics. By modifying the material surface with hydroxyl groups and constructing defects, it exhibits the characteristic of effectively degrading various microplastics at room temperature. It provides a method for obtaining high-performance photocatalyst materials through a simple and green preparation process. This invention provides a photocatalytic material and supporting technology that can effectively degrade microplastics, offering technical support for the effective removal of microplastic materials from wastewater.

[0027] (3) During the photoaging process of microplastics, hydroxyl radicals can initiate the cleavage of polymer carbon chains, playing a crucial role in the aging and degradation of microplastics. Modifying the surface of BiOCl with hydroxyl functional groups can promote the generation of more hydroxyl radicals during photoirradiation. This invention obtains the optimal photocatalytic material G / BOC-15 by controlling the glucose content during the synthesis process, i.e., controlling the surface hydroxyl content of the catalyst. Attached Figure Description

[0028] Figure 1 These are the XRD patterns of all the photocatalysts prepared in Example 1 of this invention;

[0029] Figure 2 Here are SEM images of all the photocatalysts prepared in Example 1 of this invention: (a) is BOC, (b) is G / BOC-7, (c) is G / BOC-10, (d) is G / BOC-15 and (e) is G / BOC-20;

[0030] Figure 3 These are the infrared spectra of all the photocatalysts prepared in Example 1 of this invention;

[0031] Figure 4The results show (a) the weight loss rate of all catalysts prepared in Example 1 for degrading microplastics and the catalytic performance of the photocatalyst, and (b) the correlation between the weight loss rate and the concentration of surface-modified hydroxyl groups. Detailed Implementation

[0032] The following examples further illustrate the above-described content of the present invention, but it should not be construed as limiting the scope of the subject matter of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention.

[0033] Example 1

[0034] 1) Add 4.8 mmol of Bi(NO3)35H2O and 4.8 mmol of potassium chloride to a mixture of 28 mL of ethanol and 12 mL of water.

[0035] 2) Dissolve a certain amount of 0.0875g (7%), 0.125g (10%), 0.1875g (15%), and 0.25g (20%) of α-D-glucose in a mixture of 20mL of water and ethanol (the volume ratio of water to ethanol is 1:1).

[0036] 3) Then add the glucose solution from step (2) to the mixture from step (1) and stir continuously for 60 minutes.

[0037] 4) Transfer the final solution to a polytetrafluoroethylene high-pressure reactor, then heat it to 100-150℃ and perform a hydrothermal reaction for 10 hours.

[0038] 5) Collect the product, rinse it alternately with deionized water and ethanol, and then dry it overnight in a drying oven at 60°C.

[0039] During the synthesis process, the mass ratios of α-D-glucose to BiOCl were 7%, 10%, 15%, and 20%, respectively, and the resulting BiOCl products were labeled as G / BOC-7, G / BOC-10, G / BOC-15, and G / BOC-20, respectively.

[0040] As a control experiment, samples prepared using the same method without the addition of glucose in step (2) were labeled as BOC.

[0041] The heterojunction catalyst prepared in Example 1 was subjected to phase analysis by XRD and morphological characterization by SEM. Figure 1 As shown, the XRD characterization results confirm that the material is BiOCl, card number No. 04-007-4915. Furthermore, as the amount of glucose increases, the ratio of the peak intensity of the (102) crystal plane to other characteristic peaks such as the (110) plane gradually increases, which also indicates that the (101) crystal plane is gradually exposed during this process.

[0042] from Figure 2 SEM characterization results show that the morphology of the synthesized catalyst changes significantly with increasing glucose content during synthesis. Under the influence of glucose, the initial plate-like structure of BOC spontaneously assembles into a flower-like microsphere structure, and the edges of the plate-like structure gradually become granular. When the glucose content increases to 15% by mass, the overall morphology of G / BOC-15 is a spherical structure formed by the aggregation of nanoparticles with a particle size of 30-50 nm. As the glucose content further increases to 20%, the excessively high concentration of glucose can act as a template, causing the small particles to reassemble into a plate-like structure and aggregate into a microsphere structure (G / BOC-20).

[0043] Figure 3 The Fourier transform infrared (FT-IR) spectrum is shown at 1630 cm⁻¹. -1 and 3445cm -1 The absorption peaks at the locations correspond to the stretching vibration modes of adsorbed water molecules and surface hydroxyl groups, respectively. The strongest peaks are found at both G / BOC-15 locations, indicating that the hydroxyl content is the highest. However, the excessively high concentration of glucose (20%) is sacrificed as a growth template, resulting in a decrease in the content of surface hydroxyl functional groups.

[0044] This also confirms that by controlling the glucose content during the synthesis process, i.e., controlling the surface hydroxyl content of the catalyst, we can obtain the best-performing photocatalytic material G / BOC-15.

[0045] Example 2

[0046] The photocatalytic degradation of polystyrene microplastics was carried out using a photoreaction instrument under the influence of a 500W Hg lamp.

[0047] First, 1 g / L of micron-sized plastic was dispersed in 100 mL of aqueous solution. Then, 0.5 g / L of photocatalyst was added to the solution. After reacting for 12 hours, the light source was turned off, and the solution was filtered through an aqueous system membrane with a pore size of 0.45 μm (the membrane was dried 24 hours in advance). The filtered membrane and the mixture of microplastics and photocatalyst on the membrane were removed, dried at 60°C for 24 hours, and weighed.

[0048] The results are as follows Figure 4 As shown in (a), the weight loss rate of PS-MPs under direct UV irradiation was 12.8%. BOC and G / BOC-X significantly accelerated the photodegradation of PS-MPs (the weight loss range of PS-MPs was 20-38%), among which the presence of G / BOC-15 resulted in the highest weight loss rate of PS-MPs, achieving a degradation weight loss rate of 38% for polystyrene microplastics in 12 hours, demonstrating excellent catalytic degradation performance for polystyrene microplastics.

[0049] According to the formula The photodegradation efficiency (ξ) of the photocatalyst is calculated. This is an important indicator for evaluating the activity of the photocatalyst and can be used to reflect the degree of acceleration of the photocatalyst. WL1 and WL0 are the photodegradation rates in the presence and absence of BOC or G / BOC-X, respectively.

[0050] according to Figure 4 (a) It can be seen that after 12 hours of irradiation, the photodegradation efficiency ξ values ​​of the photocatalyst are 50% (BOC), 100% (G / BOC-7), 120% (G / BOC-10), 160% (G / BOC-15), and 55% (G / BOC-20).

[0051] G / BOC-15 exhibits significantly superior photocatalytic performance compared to other compounds. To further investigate the effect of surface hydroxyl groups on MP degradation, linear regression analysis was used to examine the relationship between the MP weight loss rate and the content of hydroxyl functional groups on the photocatalyst surface. The fitting results are as follows: Figure 4 As shown in (b), the two are positively correlated. When the content of hydroxyl functional groups on the material surface is about 15%, the performance of PS-MPs reaches 160% when the photodegradation efficiency reaches 160%.

[0052] G / BOC-15 also exhibits excellent catalytic performance in the degradation of different types of microplastics. Under the same degradation conditions, the weight loss rates for polylactic acid, polystyrene, polybutylene terephthalate and polyvinyl chloride are 73%, 38%, 28% and 25%, respectively.

[0053] Example 3

[0054] Unlike step (2) in Example 1, D+(-) glucose was used instead of aD-glucose for the same proportion of surface hydroxyl functional groups modification. The degradation performance test of PS microplastics under the same conditions showed that the weight loss rate of PS modified with D+(-) glucose was 15%, while the weight loss rate of PS modified with aD-glucose was 38%. The photocatalytic degradation performance of microplastics modified with aD-glucose was 2.53 times that of D+(-) glucose.

[0055] The present invention is not limited to the specific technical solutions described in the above embodiments. All technical solutions formed by equivalent substitutions are within the scope of protection claimed by the present invention.

Claims

1. A method for using a surface-hydroxyl-modified defective bismuth halide photocatalytic material to degrade microplastics, characterized in that: The specific steps are as follows: (1) Add 4.8 mmol of Bi(NO3)3·5H2O and 4.8 mmol of potassium chloride to a mixture of 28 mL of ethanol and 12 mL of water; (2) Dissolve 0.1875 g of α-D-glucose in a mixture of 20 mL of water and ethanol, with a volume ratio of water to ethanol of 1:1; (3) Then add the glucose solution prepared in step (2) dropwise into the mixture in step (1) and stir continuously for 60 min; (4) Transfer the final solution to a polytetrafluoroethylene high-pressure reactor and heat it to 100-150 °C for hydrothermal reaction for 10 h; (5) Collect the product obtained in step (4), rinse it alternately with deionized water and ethanol, and then dry it overnight in a drying oven at 60 °C. The mass ratio of α-D-glucose to BiOCl is 15%, and the obtained BiOCl product is labeled as G / BOC-15. (6) Under the action of a 500 W Hg lamp, 1 g / L of micron-sized plastic PS-MPs were dispersed in 100 mL of aqueous solution. Then, 0.5 g / L of photocatalyst G / BOC-15 was added to the above solution. The photocatalytic degradation of microplastic PS-MPs was carried out using a photocatalytic reaction instrument. After 12 hours of reaction, the light source was turned off, and the solution was filtered using a water system filter membrane with a pore size of 0.45 μm.

2. The method for using the surface-hydroxyl-modified defective bismuth halide photocatalytic material according to claim 1 for degrading microplastics, characterized in that: Under direct ultraviolet irradiation, the presence of G / BOC-15 enables polystyrene microplastics to achieve a degradation weight loss rate of 38% within 12 hours.

Citation Information

Patent Citations

  • Preparation method of BiOCl photocatalyst, prepared photocatalyst and application of prepared photocatalyst

    CN107159274A

  • Universal synthesis method of high-activity sugar modified bismuth oxyhalide photocatalytic material

    CN111921542A